Effect of pressure and temperature in the extraction of bencilo's isotiocianato for flown supercritics from leaves gives Tropaeolum majus L. - Espinoza Silva, Clara (2017)
Tropaeolum majus L. is a native plant to South and Central America, used since ancient times by our ancestors to combat different diseases. Glucotropaeolonin is one of its main components, which when hydrolyzed forms benzyl isothiocyanate (BIT) that promotes cellular apoptosis (programmed cell death in cancer cells). Therefore, the present research aims to evaluate the effect of the pressure and temperature of benzyl isothiocyanate extraction by supercritical CO2 from Tropaeolum majus L. The extraction was carried out in a supercritical fluid extractor equipment Speed SFE BASIC Brand: Poly science, the leaves of Tropaeolum majus L. were ground for one hour and lyophilized until obtaining a humidity of 6%. The extraction with supercritical CO2 was carried out with pressures of 200 and 300 bar, temperatures of 50 °C, 60 °C and 70 C, obtaining by the conjugation of these six treatments. Benzyl isothiocyanate was identified by thin layer chromatography using 98% benzyl isothiocyanate as the standard, and as the mobile phase hexane: dichloromethane (4: 2). Subsequently benzyl isothiocyanate quantification was performed by high performance liquid chromatography (HPLC). The highest yield of oleoresin by supercritical CO2 extraction was obtained pressure 300 bar and temperature at 60 °C (35. 67%); and the higher content of benzyl isothiocyanate at pressure 200 Bar and 70 °C for 30 minutes to obtain 113.615 ± 0.03 mg BIT / 100 g dry matter was obtained.